(untitled) - Moore, John T. (Indianapolis, IN, 2006)
The author takes you from the very basic "what is an atom" and "how to read the periodic table" to more advanced concepts such as Nuclear Chemistry, with consumate ease. The book throughout is structured for the (nearly) absolute beginner, with few assumptions being made about your beginning level of knowledge.
Keywords: Chemistry,Hóa học